Greenhouse evaluation of Great Plains native grasses and forbs tolerance to postemergence herbicides used for roadside weed control - Rachel C. Woody-Pumford; Matthew B. Bertucci; Mike D. Richardson; Dirk Philipp; Hannah E. Wright-Smith (Weed Technology, 2025)
To combat the decline in North American grasslands and prairies, innovative strategies to establish new native grass and forb plantings must be considered. Integrated vegetation management entails the use of many practices to cultivate desirable vegetation along roadsides, including mowing, applying herbicides, burning, and replanting. Currently, only a limited selection of postemergence herbicides are available to improve native plant establishment along roadsides. A greenhouse herbicide screen that included four postemergence herbicides registered for use on Conservation Reserve Program (CRP) acres and rights-of-way was conducted to test their safety for use on four native grasses (big bluestem, buffalograss, sideoats grama, and switchgrass) and seven forb species (ashy sunflower, black-eyed Susan, butterfly milkweed, desert false indigo, Illinois bundleflower, Mexican hat plant, and purple coneflower). Clopyralid (689 g ae ha−1), metsulfuron (4.18 g ai ha−1), and quinclorac (418 g ai ha−1) applied at labeled rates caused no injury to the native grass species or butterfly milkweed. However, florpyrauxifen-benzyl (38.4 g ai ha−1) caused significant injury to buffalograss and switchgrass. None of the herbicides tested were universally safe to use on all forb species evaluated in this trial, with each herbicide causing unacceptable injury (≥25%) to one or more forb species. None of the herbicides studied here would be completely safe for use on mixed stands of native grasses and native forbs at the seedling growth stage, indicating that prairie establishment must use alternative chemistries, plant mixes with fewer species, or avoid postemergence applications shortly after emergence of native forbs.